2016
DOI: 10.1093/abbs/gmw002
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte populations and IL-6 in the tumor microenvironment of an orthotopic colorectal cancer model

Abstract: Colorectal cancer (CRC) is a major health problem worldwide. It is often diagnosed late due to its asymptomatic nature. As with all cancers, an immune reaction is involved; however, in CRC, it is unknown if this immune response is favorable or unfavorable for disease progression. In this study, the immune response in mesenteric lymph nodes (MLNs) and Peyer's patches was investigated during development of CRC in an orthotopic mouse model. CRC was induced by injecting CT26 cells into the cecum wall of BALB/c mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
(41 reference statements)
1
15
0
1
Order By: Relevance
“…Orthotopic tumors were better infiltrated with T cells than subcutaneous tumors, same trend was also observed with B cells. Similar results were also observed in a cecum model [ 26 ], in which higher frequency of CD8 + T cells were detected in Peyer's patches in response to tumor challenge. Furthermore, studies have shown that regulatory T-cell (Treg) inhibits the function of cytotoxic T-cell and selectively kills antigen presenting cells including B cells [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Orthotopic tumors were better infiltrated with T cells than subcutaneous tumors, same trend was also observed with B cells. Similar results were also observed in a cecum model [ 26 ], in which higher frequency of CD8 + T cells were detected in Peyer's patches in response to tumor challenge. Furthermore, studies have shown that regulatory T-cell (Treg) inhibits the function of cytotoxic T-cell and selectively kills antigen presenting cells including B cells [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…In mice, orthotopic tumors had more NK-cell infiltration than subcutaneous tumors. In a caecum model, higher levels of NK cells were founded in mesenteric lymph nodes (MLNs) of tumor group compared with MLNs of control groups [ 26 ]. Notably, subcutaneous tumors had more immunosuppressive cells such as MDSCs, compared to orthotopic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo tissues (CD45 + TILs) and cells of another murine CRC cell line (CT26), obtained from a BALB/c mouse, showed a positive reaction to IL-6, indicating this cytokine as key for CRC TME. Moreover, it could also potentially participate in CRC-associated cachexia [ 96 ].…”
Section: The Role Of Tumor Microenvironment (Tme) Cells In Crc-assmentioning
confidence: 99%
“…Advances in the understanding of the TME in pre-invasive and invasive breast cancer have demonstrated strong evidence to suggest that the TME and associated molecules as well as the infiltration of immune cells, soluble factors and altered extracellular matrix, are involved in promoting tumor growth and metastasis [51,52]. These critical elements of the TME have initiated the identification of new breast cancer markers, such as biological, immunological and immunosuppressive which are associated with tumor development and progression [53].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%